Menjadi Gereja Kaum Miskin Suatu Refleksi Teologi dan Dialog Antara Gereja dan Kaum Miskin dalam Konteks Kemiskinan di Indonesia - Dismas Kwirinus; Heribertus Peri (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2023)
The focus of this research examines the Church of the Poor. The topic of study is related to encounters and dialogue between churches and poor communities in the context of poverty in Indonesia. In the midst of a poverty situation like that which occurs in Indonesia, the church is invited to fulfill its calling. In situations like this, it is clear that the church cannot simply be a donor or Santa organization. This means that to realize its call to the poor, the church must have the courage to become a "Church of the Poor". This research was conducted using qualitative descriptive methods and critical reading of texts, namely: (1) Documents of the Second Vatican Council; (2) FABC (Federation of Asian Catholic Bishops' Conferences) documents; (3) Books about the Church of the Poor; (4) Scientific articles about the Church of the Poor. The findings in this research are that what is meant by "church of the poor" here is a church that not only fights for the poor but more than that, a church that is willing to take sides and fight with them. The church must also dare to be open, willing to accept the poor as they are, and eliminate the dividing lines between themselves and the poor so that dialogue can occur between the two. The dialogue between the church and the poor here is a dialogue of life. Dialogue of life means dialogue that is based on accepting the poor as they are and making their problems and struggles to achieve true humanity the problems and struggles of the church as well.